PENGARUH BIAYA PROMOSI TERHADAP VOLUME PENJUALAN GENTENG PADA PT. CAHAYA BANGUN JAYA PERKASA MAKASSAR - Guntur Suryo Putro (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
The purpose of this study is to determine the effect of promotion costs on the sales volume of tiles at PT. Cahaya Bangun Jaya Perkasa Makassar. The research method used is correlation analysis and determination analysis. The results of this study indicate that the promotional costs that have been issued by PT. Cahaya Bangun Jaya Perkasa Makassar. Every year Promotional Cost increases, The volume of tile sales has increased in each year. The effect of promotional costs on tile sales volume, calculated by statistical analysis. From result of calculation hence relation between variable X (Cost of Promotion) and Y (sales volume) equal to r = 0,782 result show higher value X (Promotion Cost), it will be bigger also Y (sales volume), then counted how big influence Promotion cost to sales volume by using Coefficient of Determination is KD = (0,782) 2 x 100% = 0.6121 means that the average value of sales volume of 61.21% is determined by promotional costs that have been issued company. And from the regression equation obtained results Y = 46.761 + 0.921 (x)